Web-Based Gamification: Problems in EFL Classroom of Higher Education Due to Online Assessment Employment - Pitoyo, Muhammad Dafit (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
Gamification is considered new concept in education especially in assessment in which the idea of using elements of game to create engaging assessment. Assessment is really important in education due to its function to get valid and rich information of the students’ test which will be utilized as the tool to make betterment in teaching and learning process. This article will discuss gamification application within assessment environment: implementation problems and its solutions. The researcher will use qualitative case study for this research. Qualitative case study methodology offers tools for researchers to investigate and understand complex phenomena in their contexts. The respondents of this research will be students of higher education and a lecturer who has used gamification for assessment for years in his class. This article will reveal the picture of gamification test mechanism. Furthermore, it is able to promote technology in education in this century to facilitate teaching and learning process.